تأمّلات حول الطلاق في ضوء سورة الطلاق رؤية نفسية تربوية اجتماعية - Ali, A. H. (Universiti Sains Islam Malaysia, 2024)
This article tries to reveal the most important reasons for divorce as mentioned in the Surat al-Talaq (The Divorce). It tries to show some of the psychological guiding aspects that the Quran enlightened regarding divorce. Thus, to deal with the topic, this article will discuss some of the following aspects: the name of the Surah, the time of its revelation, its order in the Holy Koran, the opening of the Surah, the prescribed period of a divorced wife and where should she spend etc.